Evaluation of stat-modifying small molecules for mediating macrophage polarization - Salim, Arief Tjitra (2018)
Contact with biomaterials has been shown to induce macrophage polarization towards the pro-inflammatory M1 and anti-inflammatory M2 phenotypes, with implications on clinical outcomes of the affected device. Recent studies suggest STAT1 and STAT3 activation of the JAK/STAT signaling pathway to have central roles in macrophage polarization. Here, the novel treatment of modulating M1 and M2 macrophage phenotypes by small molecule inhibition of STAT3 and STAT1 activation, respectively, was studied. The hypothesis in this study was that STAT inhibitor small molecules can be used to manipulate macrophage polarization. To test this hypothesis, a quantitative reverse transcriptase polymerase chain reaction (RT-qPCR) assay was first developed to profile gene expression changes during the molecule–induced macrophage polarization process. Subsequently, a panel of small molecules were selected and evaluated for macrophage polarization activity. Seven out of the nine STAT3 inhibitor small molecules screened (Stattic, S3I-201, Niclosamide, HO-3867, BP-1-102, SH5-07, Cryptotanshinone) were shown to upregulate the selected M1 markers (IL-6, IL-8, TNF-a), while five out of the seven screened STAT1 inhibitor small molecules (Fludarabine, Curcumin, Apigenin, Luteolin, Paeonol) were shown to upregulate two (DC-SIGN, Dectin-1) out of the three selected M2 markers, indicating successful macrophage polarization. Overall, the findings suggest the potential utility of small molecules for the modification of macrophage behavior. Additionally, the quantitative RT-qPCR assay developed in this project proved to be useful as a screening method to evaluate macrophage phenotype modifying behavior of pharmaceutics and /or biomaterials.